Dawn completes its mission at 4 Vesta. (10th April 2013) - Russell, C. T.; Raymond, C. A.; Jaumann, R.; McSween, H. Y.; De, M. C.; Nathues, A.; Prettyman, T. H.; Ammannito, E.; Reddy, V.; Preusker, F.; O'Brien, D. P.; Marchi, S.; et al.
Abstract The Dawn mission was designed to test our hypothesis about the origin and evolution of the early solar system by visiting the largest differentiated basaltic asteroid, 4 Vesta, believed to be a survivor from the earliest times of rocky body formation. Observations from orbit show that Vesta is the parent body of the Howardite, Eucrite, Diogenite meteorites. Vesta has an iron core and a eucritic–diogenitic crust. Its surface is characterized by abundant impact craters but with no evident volcanic features. It has two ancient impact basins in the southern hemisphere that are associated with circum‐planetary troughs. The northern hemisphere is the more heavily cratered and contains the oldest terrains. The surface of Vesta is diverse, with north‐south and east‐west dichotomies in the eucrite‐to‐diogenite ratio. Its surface contains both very bright and very dark material, and its color varies strongly from region to region. Both the mineralogical and the elemental compositions agree with that expected for the HED parent body. Significant OH or H may be present in the upper crust and the presence of pits in "fresh" craters is consistent with the devolatilization of the surface after a collision either brought to or tapped a source of water on Vesta. The presence of dark material on the surface of Vesta suggests efficient transport pathways for organic material, and the mixing of the dark material with the more pristine pyroxene explains the varying albedo across the surface. Vesta has proven to be a reliable witness to the formation of the solar system.